Analysis of the Influence of Brand Image, Price, and Product Quality on Consumer Buying Intentions in the Indonesian Retail Market: Mediation by the Level of Consumer Trust - Yuliastuti, Hilda; Mulyono, Sri; Krisprimandoyo, Denpharanto Agung; Jusman, Ikhsan Amar (International Journal of Business, Law, and Education, 2024)
This research investigates the complex dynamics influencing consumer behavior in the Indonesian retail market, focusing on the interrelationships between brand image, price, product quality, consumer trust, and consumer buying intentions. Utilizing a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis, data was collected through a survey of 100 respondents. The results reveal significant positive relationships between brand image, price, product quality, and consumer buying intentions, highlighting the pivotal role of these factors in shaping consumer preferences and purchase decisions. Furthermore, the study identifies consumer trust as a mediating factor, emphasizing its importance in strengthening the relationship between brand image and consumer buying intentions. The practical implications of these findings for retailers and marketers are discussed, emphasizing the importance of strategic brand management, pricing strategies, product quality enhancement, and trust-building initiatives to drive consumer behavior and achieve long-term success in the Indonesian retail market.